Persepsi Mahasiswa PGSD Universitas Jambi Terhadap MK Tari Melayu Jambi - Alirmansyah Alirmansyah; Destrinelli Destrinelli; M Sargandi; Stevie Yolanda; Novita Wisudawati; Windy Lara S. Samosir; Anggi Kurnia; Chindy Nurlayly (JPKS (Jurnal Pendidikan dan Kajian Seni), 2019)
Abstract : This study aims to examine and describe the perception of PGSD Jambi University Students Against the Malay Dance Court, the research is expected to be able to find the right perception of the Malay dance MK by PGSD students. This research uses a qualitative approach. Data collected using observation, interviews, and documentation. The results of this study show that in the eyes of PGD students at first the Malay dance dance was very difficult but due to the learning process of the Malay dance dance itself was cool then it made the students remember to follow the process proven by the various achievements of elementary school teacher education students, in addition to the achievements of students also able to develop their potential in elementary school to be able to teach Malay dance to existing students.  Abstrak : Penelitian ini bertujuan mengkaji dan mendeskripsikan Persepsi Mahasiswa PGSD Universitas Jambi Terhadap MK Tari Melayu, penelitian diharapkan mampu menemukan persepsi yang tepat terhadap MK tari melayu oleh Mahasiswa PGSD. Penelitian ini menggunakan pendekatan kualitatif. Data dikumpulkan menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahawa dalam pandangan mahasiswa pgsd  pada awalnya tarii melayu jambi sangatlah sulit namun dikarenakan proses pembelajaran tari melayu jambi itu sendiri asik maka membuat mahasiswa semngat  mengikuti proses yang terbukti dengan berbagaiprestasi yang di  raih mahasiswa Pendidikan Guru Sekolah Dasar, selain prestasi yang diraih mahasiswa juga mampu mengemangkan potensi dirinya di sekolah dasar untuk mampu mengajar tari melayu jambi  kepada peserta didik  yang ada .